Nurses’ Role in Spirometry Testing - Yuenyong, Somruthai; Tocharoennirattisai, Ittiwat (Siriraj Medical Bulletin, 2020)
Spirometry is the most common type of pulmonary function testing that can be used for assess ,diagnose and to follow various lung conditions. Nurses are medical personnel that are closest to patients,this article is intended to help nurses to know and understanding about spirometry testing and help patients undergoing testing with safely. In addition, this article describes the practice nurses in the role of spirometry technician, who have completed a spirometry course that cetified by the Thoracic Society of thailand.